Sustaining Rice Production through Biofertilization with N2-Fixing Cyanobacteria - Macarena Iniesta-Pallarés; Consolación Álvarez; Francisco M. Gordillo-Cantón; Carmen Ramírez-Moncayo; Pilar Alves-Martínez; Fernando P. Molina-Heredia; Vicente Mariscal (Applied Sciences, 2021)
Current agricultural productivity depends on an exogenous nutrient supply to crops. This is of special relevance in cereal production, a fundamental part of the trophic chain that plays a vital role in the human diet. However, our agricultural practices entail highly detrimental side-effects from an environmental point of view. Long-term nitrogen fertilization in croplands results in degradation of soil, water, and air quality, producing eutrophication and subsequently contributing to global warming. In accordance with this, there is a biotechnological interest in using nitrogen-fixing microorganisms to enhance crop growth without adding chemically synthesized nitrogen fertilizers. This is particularly beneficial in paddy fields, where about 60% of the synthetic fertilizer that has been applied is dissolved in the water and washed away. In these agricultural systems, N2-fixing cyanobacteria show a promising biotechnological potential as biofertilizers, improving soil fertility while reducing the environmental impact of the agricultural practice. In the current study, Andalusian paddy fields have been explored to isolate N2-fixing cyanobacteria. These endogenous microorganisms have been subsequently re-introduced in a field trial in order to enhance rice production. Our results provide valuable insights regarding the use of an alternative natural source of nitrogen for rice production.